Community attitudes to road safety : community attitudes survey wave 8 - Adams, Kathryn, 1963-; Mitchell-Taverner, Philip (CR, 1995)
This report contains a summary of results from the survey conducted in May/June 1995 and, where appropriate, provides comparative findings in relation to previous surveys. Issues examined include: perceived causes of road crashes, exposure to random breath testing, attitudes to drink driving, attitudes to speed, perceptions of police enforcement, seat belt usage and involvement in road crashes. Community attitudes. Surveys. Random breath testing. Public opinion. Speed. Drink driving. Enforcement. Perception. Seat belts. Occupant restraints.